Congenital Antral Web in Premature Baby - Nam, So-Hyun (The Korean Society of Pediatric Gastroenterology, Hepatology and Nutrition, 2013)
Antral web is a rare cause of gastric outlet obstruction in neonate. It is a 2-4 mm thin mucous membrane that can be found anywhere from 1 to 7 cm proximal to the pylorus. The baby was born at gestational age of 32(+1) weeks with 1,880 g as 2nd baby of dizygotic twin. After birth, the baby had constant non-bilious vomiting without feeding while he didn't show abdominal distension or discoloration. The infantogram showed distended stomach with distal small bowel gas. Upper gastrointestinal series revealed that the antrum was abruptly narrowed at 1 cm proximal to pylorus. We performed laparotomy at the 10th day after birth and excised the 2 mm-thick web circumferentially. He began milk feeding after 6 days and discharged uneventfully at postoperative 35 days with corrected age of 38(+4) weeks with body weight 2,420 g. The antral web should be considered in the case of non-bilious vomiting in neonate.